Biomechanical evaluation - Fernandes, R. (FINA World Sports Medicine Congress, 18, 2016)
Prof. Ricardo Fernandes, University of Porto (POR) talks about "Are the New Starting Block Facilities Beneficial for Backstroke Start Performance? (Biomechanical Evaluation for Perfecting Swimmers` Technique)" at the FINA World Sports Medicine Congress 2016. (19:20 min)